Power and Contestation: India Since 1989 - Shrivastava, Meenal (Labour / Le Travail, 2008)
The article reviews the book, "Power and Contestation: India Since 1989," by Nivedita Menon and Aditya Nigam.
Keywords: 20th century; BOOKS – Reviews; History; INDIA; MENON; Nivedita; NIGAM; Aditya; Nonfiction; POWER & Contestation: India Since 1989 (Book)